Mid-infrared spectroscopy: Screening method for analysis of food adulterants in reconstituted skimmed milk powder. (June 2022) - Da Costa Filho, Paulo Augusto; Chen, Yike; Cavin, Christophe; Galluzzo, Roberto
Abstract: This study successfully shows that MilkoScan™ FT1 can be employed as rapid screening technology for detecting sixteen out of twenty-one food adulterants in reconstituted skimmed milk powder. The validation of untargeted fingerprinting method correctly identified 100% of unadulterated samples and 93% of samples adulterated with nitrogen-rich compounds or bulking agents at 5% economical adulteration. Furthermore, this work shows that lactose is a challenging adulterant to be detected by an untargeted screening method because it is naturally present in skimmed milk powder. However, this study showed that specific calibration can be applied to detect addition of lactose in skimmed milk powder. As a result, this method of screening displays a high potential to be employed by various food businesses (such as dairy, confectionary and infant formula, etc.) to rapid screening of raw materials and detect abnormalities, which may be linked to food adulteration or quality defects, ensuring products of better quality and safety to consumers. Highlights: Detection of food adulterants in reconstituted skim milk powder using mid-infrared. Untargeted screening method for detection of nitrogen-rich compounds and bulking agents. The adulterated and unadulterated samples show sensitivity of 93% and 100%, respectively.